Improving Grammar Mastery through Movie Segment for the Fourth Semester of English Students academic year 2018/2019 at Madura Islamic University - setiyawan, arisandi (Lingual Journal of Language and Culture; Vol 8 No 2 (2019): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2019.v08.i02.p06, 2020)
Grammar learning in the class is not delivered attractively so that it can cause students to have low enthusiasm for learning. Besides, monotonous learning makes students easily get bored. After understanding the importance of grammar in learning English, it is needed to have learning media that can solve students' problems in class. Researchers offer instructional media in the form of authentic material that is a movie segment to be applied in learning grammar. The purpose of this research is to find out how the movie segment can improve the grammar mastery of fourth-semester students. The use of authentic material in the classroom can create a pleasant atmosphere because it can reduce anxiety levels and provide examples of English applications in the real world. Movie Segment is one type of authentic material in the form of video clips that are used to teach grammar. It is also equipped with worksheets, exercises, and answer keys so that it can facilitate the teacher to use the appropriate material and create a pleasant atmosphere in the classroom. The research design used is Classroom Action Research. Meanwhile, The criterion for success in this study is 75% of students achieve 75 in learning Grammar (Simple Past tense). The results of this study indicate that the mean value on the pre-test was 65.2 and the average value of the post-test in cycle 1 increased to 72.8. Then, the post-test mean score in cycle 2 increased to 78.8. The percentage of students who reached above or equal to KKM is 75 increased from 32% to 60% in cycle 1 and 80% in cycle 2. Therefore, this study proves that the use of movie segments can improve grammar understanding and can be used as one of alternative techniques in teaching grammar (past tense).